University Youths' Perceptions of Feminism in Uganda : case of Makerere University and Uganda Management Institute - Franklin, H. (My University, 2020)
This study was premised on the successful implementation of policies like affirmative action in education and politics leading to a rise in numbers of women joining these sectors of the Ugandan economy. The political will has led to increased women inclusion ushering in the first female speaker of parliament and female vice president on the African continent. However, with these achievements, students looked at these as just but a drop in the ocean that does not make feminism an important part in women's emancipation. The 1980's ushered in structural adjustment programmes (SAPs) introduced by the World Bank affecting Uganda's education sector (it could no longer support the sector). This led to increased demand for higher education services with the limited infrastructure leading to establishment of over 10 private universities in the country. With such new developments, female enrollment still remained low because of reduced funding, cultural bias and no clear gender equity plan. African universities most often meet needs of male students and faculty, for instance, leadership in Makerere University is still highly masculinized with less than 04 females being Deans out of 29. These women face insurmountable challenges including lack of time to mentor the younger generation. The study utilised mixed methods with 75 respondents being purposively selected. Data was collected using secondary data analysis, interviews and questionnaires. The Key findings found out that feminism was competing with Human rights, climate change and new political waves. South Africa and Kenya have the highest number of "feminists' aware students" and Uganda (with gender sensitive policies) is still grappling with equality issues. This could impede adaptation of feminist thought amongst university youths hence promoting inequality in the society. Some of the recommendations included; increased sensitization and advocacy, redefinition of feminism to include climatic debate, human rights coupled with bringing on board the male child. Keywords: Access, Feminism, Higher Education, Rebranding of feminism, University Students
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Access; Feminism; Higher education; Rebranding of feminism; University Students; Affirmative action programs; Affirmative action programs in education; College students